Comparative Study of the Performance Behaviour of Solar PV Modules in Kitui County - Wekesa, David (My University, 2018)
Solar energy technology is emerging alternative energy source to meet specific demands around the world. The research will identify and focus on performance behavior of solar PV modules at selected sites whose geographical parameters such as latitude, insolation, altitude and other installation design factors will be identified. the current-voltage and power-voltage characteristics at STC will be measured and recorded for each module at the Centre for Renewable Energy at Machakos University before installation for a period of six months. Daily climate parameter such as ambient temperature, humidity, air mass, wind speed and rainfall data will be recorded alongside the daily maximum current, voltage and power output of each PV module for the set period. The data collect will be analyzed to indicate whether the climatic, geographical and ambient variations in the region have significant effect on the performance ratio of PV module types. Hopefully, the findings of this research will give a comparative and predictive performance behavior for PV modules in the corresponding climatic region that can guide manufacturers, suppliers, consumers and potentially open a path to developing a third standard for PV Modules Testing standards for different regions in Kenya.
Keywords: Solar PV; Performance behaviour; STC; Solar module; Climate